STYLAGE®: a range of hyaluronic acid dermal fillers containing mannitol. Physical properties and review of the literature - Ramos-; Fonteles LA; Lagalhard CSX; Fucci- (Dove Medical Press, 2013)
Marcia Ramos-e-Silva, Lívia Arcanjo Fonteles, Cecília Schubert Xavier Lagalhard, Ana Paula Cercal Fucci-da-CostaSector of Dermatology, University Hospital and School of Medicine, Federal University of Rio de Janeiro, Rio de Janeiro, BrazilAbstract: Dermatological procedures which are considered as being minimally invasive, such as those using injectable fillers based on hyaluronic acid, revolutionized aging treatment, especially of the face. By promoting the replacement of lost volume and attenuating grooves and wrinkles, they ensure a more youthful appearance and certain functional recovery of facial aesthetics. The authors review some of the main physicochemical characteristics of these dermal fillers, highlighting the product line Stylage®, the manufacture of which includes mannitol.Keywords: fillers, hyaluronic acid, mannitol, facial aging, wrinkles, stylage®